MEMBANGUN DEMOKRATISASI MELALUI KETERBUKAAN INFORMASI PUBLIK : STUDI TERHADAP PERAN KOMISI INFORMASI PUBLIK (KIP) DALAM PELAKSANAAN KETERBUKAAN INFORMASI PUBLIK DI LINGKUP INSTITUSI PEMERINTAH DAERAH KALIMANTAN TENGAH - Ade Rian Riwandy (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2016)
This thesis research the topic of The Role of Information Commission Central Kalimantan province. Information Commissioner of Central Kalimantan is one of the institutions established by the Regional Independent Regional Head in Central Kalimantan province, has the main function of helping people resolve problems related to Public Information. This research was conducted at the Central Information Commission Kalimantan city of Palangkaraya using descriptive qualitative method. The purpose of this research is to know What is the Role of Information Commission Central Kalimantan in order to help people resolve problems related to public information in Central Kalimantan and the factors that support and hinder the performance of Central Kalimantan Information Commission in carrying out their duties and functions. The results of this study explained that the Information Commissioner of Central Kalimantan as regional institutions to help resolve disputes of public information in the province of Central Kalimantan is already functioning as it should, but not Optimal. Not optimal role of the Information Commissioner of Central Kalimantan which is becoming the main problem is the lack of attention factor Provincial Government of Central Kalimantan on the existence of the Information Commission itself in Central Kalimantan. The lack of attention is evidenced by the lack of budget APBD given to sustainability and the future existence of this institution. The lack of budget to make these institutions less able to move mainly socialize existence for the people of Central Kalimantan.